2013
DOI: 10.1111/1574-6941.12145
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial invasion potential in water is determined by nutrient availability and the indigenous community

Abstract: In drinking water (DW) and the distribution systems, bacterial growth and biofilm formation have to be controlled both for limiting taste or odour development and preventing clogging or biocorrosion problems. After a contamination with undesired bacteria, factors like nutrient availability and temperature will influence the survival of these invaders. Understanding the conditions enabling invaders to proliferate is essential for a holistic approach towards microbial risk assessment in DW. Pseudomonas putida wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 61 publications
2
45
0
Order By: Relevance
“…Recent work aimed at understanding the potential for pathogen proliferation in drinking water systems revealed that pathogens were outcompeted by native microbial communities adapted to life in drinking water [46,47]. These results reinforce the recommendation to isolate pesticide degraders from environments and under conditions that are similar to those in which the bioaugmentation will occur [36 ].…”
Section: Bioaugmentation In Pesticide-contaminated Water Resourcesmentioning
confidence: 57%
“…Recent work aimed at understanding the potential for pathogen proliferation in drinking water systems revealed that pathogens were outcompeted by native microbial communities adapted to life in drinking water [46,47]. These results reinforce the recommendation to isolate pesticide degraders from environments and under conditions that are similar to those in which the bioaugmentation will occur [36 ].…”
Section: Bioaugmentation In Pesticide-contaminated Water Resourcesmentioning
confidence: 57%
“…Previous studies showed the same antagonism (Chandran and Mohamed Hatha, 2005;Vital et al, 2012;Van Nevel et al, 2013). Antagonism may arise FIGURE 4 | Inactivation of E. coli at various conditions during (A,B) chlorination and (C) electrolysis.…”
Section: Indigenous Microbial Communitymentioning
confidence: 77%
“…Therefore, for further measurements the frequency was set at 100Hz, selected based on the literature [14]. Subsequently, the measurement of biofilm was carried out continuously in flow conditions for 30 days [15]. The measurements were carried out at intervals of 10 seconds.…”
Section: Resultsmentioning
confidence: 99%